Academic Conference Presentations A Step-by-Step Guide - Freiermuth, Mark R. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"What an immensely useful and highly readable book. This is a fantastic book for grad students - it takes readers on a journey filled with practical, concrete advice from choosing the conference, writing the abstract to presenting online and in person. It is an invaluable resource but also a truly interesting read which both engages and informs." -Sarah Mercer, Professor for Foreign Language Teaching and the Head of the ELT Research and Methodology Department, University of Graz, Austria This book provides a step-by-step journey to giving a successful academic conference presentation, taking readers through all of the potential steps along the way-from the initial idea and the abstract submission all the way up to the presentation itself. Drawing on the author's own experiences, the book highlights good and bad practices while explaining each introduced feature in a very accessible style. It provides tips on a wide range of issues such as writing up an abstract, choosing the right conference, negotiating group presentations, giving a poster presentation, what to include in a good presentation, conference proceedings and presenting at virtual or hybrid events. This book will be of particular interest to graduate students, early-career researchers and non-native speakers of English, as well as students and scholars who are interested in English for Academic Purposes, Applied Linguistics, Communication Studies and generally speaking, most of the Social Sciences. With that said, because of the book's theme, many of the principles included within will appeal to broad spectrum of academic disciplines. Mark R. Freiermuth is Professor of Applied Linguistics at Gunma Prefectural Women's University, Japan. .
Chapter 1: The Good, the Bad and the Ugly: The Reality of Academic Presentations -- Chapter 2: Getting Started: The Precision Abstract -- Chapter 3: After the Excitement Fades: Preparing and Practicing your Presentation -- Chapter 4: Group Presentations -- Chapter 5: Next up on Stage: What to Expect before, during and after your Presentation -- Chapter 6: The Seven Deadly Sins: Presentation Missteps that can and should be Avoided -- Chapter 7: Prologue. .
Keywords: Applied linguistics; Research-Methodology.; Career education; Educational sociology; Applied Linguistics; Research Skills; Career Skills; Sociology of Education